Perancangan Alat Pembuat Pelet Lele untuk Menekan Biaya Pakan dan Meningkatkan Profit pada UMKM Silurus - Reyhandoyo Putra Pratama; Hery Murnawan (SURYA TEKNIKA, 2024)
Silurus UMKM is a catfish farming business that has been operating since 2019, using the biofloc method to increase harvest efficiency. However, the main obstacle faced is the increase in fish feed prices, reducing the frequency of feeding and extending the harvest period to 3.5–4 months. As a solution, this study proposes the design of a catfish feed pellet making machine based on worker anthropometric data to ensure ergonomics. This machine is designed to utilize local waste raw materials, such as tofu dregs and bran, which are available for free or at low cost. The trial results showed that the machine can produce 3 kg of pellets per cycle with an average time of 74 seconds. The production cost analysis recorded a total expenditure of IDR 2,365,625 per harvest with a production capacity of 50 kg, resulting in a production cost (HPP) of IDR 47,312 per kilogram with the machine design being able to save HPP of 7,688 / Kg or a savings of 13.97%. The use of local raw materials such as tofu dregs and bran in feed production has a significant economic impact, reducing costs by up to 13.97%. This approach increases the profitability of MSMEs by reducing dependence on expensive commercial feed. Waste-based solutions also support long-term sustainability, integrating economic efficiency and environmental friendliness. With the implementation of this machine, Silurus MSMEs can reduce feed costs, increase production efficiency, and support business sustainability. This research provides practical solutions for similar MSMEs to overcome operational cost challenges through affordable and environmentally friendly technological innovations.